EFEKTIVITAS PENGGUNAAN MEDIA POWER POINT DALAM MENINGKATKAN TINGKAT BERPIKIR GEOMETRI SISWA KELAS 6 - Hanifa; Nuryami (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2025)
This study aims to analyze the effectiveness of using PowerPoint media in enhancing the geometric thinking skills of 6th-grade students, particularly in understanding the concepts of area, perimeter, and volume of solid figures. This research uses a quantitative approach with a quasi-experimental design (one-group pretest-posttest design) at MI Nazhatut Tholibin, Probolinggo Regency. The research subjects consist of 20 students divided into two groups: the experimental group using PowerPoint and the control group using conventional teaching methods. Data were collected through learning outcome tests, interviews, and observations. The results of the study show that the use of PowerPoint significantly improved the students' learning outcomes. Statistical tests indicate that the data is normally distributed and the variance between groups is homogeneous. The Independent Sample t-Test results show a significant difference between the experimental and control groups, with a significance value of 0.001 (p < 0.05). The posttest average score of the experimental group is higher than that of the control group, indicating the effectiveness of PowerPoint in helping students understand geometry. This study concludes that PowerPoint can be an effective alternative in mathematics learning, particularly in solid figures.